Contemporary political families and the dynamics of politics in San Joaquin, Iloilo. - Selibio, Niño Kristobal Sarria (2003.)
This study is about San Joaquin's political families, their political careers and characteristics, at the same time, the political dynamics that play in the town's politics. Furthermore, this study deals with the question on how political families and political dynamics work together in pursuit of political dominance in the municipality., This study finds that the political families evolved from different period of history - during the Spanish period, the American occupation, the pre-Martial Law era and the post-Marcos regime. These families are in better socio-economic condition, an attribute that triggers political patronage in the town. Although age and gender are less significant considerations in politics, this study has noted that mature male members dominate the families' political tradition. With the birth of Sangguniang Kabataan (SK), young members of the families hold top positions. Political parties often favor candidates from political families over other political individuals. Hence, the politics of the town have successional and generational characteristics. Political frog-hopping is rampant similar to other localities in the country. Political rivalries within a family have caused them to break-up, in the same way that political feud between families has caused violence that resulted to factionalism in the town. Political individuals outside of San Joaquin have influenced the politics of the town through political logistics and the manipulation of barangay officials as their leaders. This situation has opened doors to barangay's dynamic role in politics. This has further intensified the political factionalism in the town due to barangay officials' affiliation due to either side of the faction. The political families and local political play vital role in the politics of San Joaquin; The former as political actors and the latter as the political machine, complementing each other in pursuit of political power.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Political Families -- San Joaquin, Iloilo